A new species of eriophyoid mite (Acari: Eriophyoidea) infesting Terminalia crenulata (Heyne) from sub-Himalayan region of India - Sanjay Sarkar (Persian Journal of Acarology)
Among the Acari, eriophyoid mites are considered important pests as they produce various damage symptoms while feeding on plants. During the general surveys for eriophyoid mites of Mongalbari, Malda, West Bengal, India, one new species, Colomerus terminaliae sp. nov. of the family Eriophyidae was found along the rolling of leaf margin of Terminalia crenulata (Heyne) Roth (Combretaceae). This new phytophagous mite species is described and illustrated from the specimens collected at present study area. The new species is compared with other closely related species and a differential diagnosis is also provided here. The new species belongs to the genus Colomerus Newkirk & Keifer, 1971. This new species is morphologically distinguished from other existing species of Colomerus and it produces leaf rolling at the edges of leaves and causes damage to this economically important tree by its phytophagous mode of nutrition. For proper control of this mite pest, studying its taxonomy and relation to the host plant is essential.